Mal Pelayanan Publik Sebagai Praktik Inovasi Pemerintah Daerah Di Wilayah Provinsi Jawa Barat - Nur, Mohamad Ichsana (Sawala : Jurnal Administrasi Negara, 2023)
Public sector innovation is currently a big political and administrative agenda and is stealing attention from developed democratic countries, and following it to a number of other developing countries. In the context of Indonesia as a developing country, the Government is committed to continuing to support public service innovation through a series of existing rules and regulations. West Java is included in the top five highly innovative provincial government versions of the Ministry of Home Affairs of the Republic of Indonesia. Of the 27 regencies/cities in West Java, it seems that Bekasi City is the only region that has succeeded in developing its government innovations in a good and superior manner. It was recorded that from 2018 to 2021, the Regional Government of Bekasi City through the Investment Service and One-Stop Integrated Services received an award as a public service provider in the "Prime Service" category. This good achievement is known because the Regional Government of Bekasi City has succeeded in building and developing a Public Service Mall in the area effectively. Thus, this study aims to analyze the practice of local government innovation in Bekasi City, especially how the Public Service Mall in the City organizes its innovations. The results of this study indicate that the existence of the Bekasi City Public Service Mall is able to make its citizens more satisfied and trust the Regional Government. The Bekasi City Government, through its DPMPTSP, has won awards in the category of innovative public services several times. Indeed, this award is an encouraging bonus from efforts to provide public services that are able to bring benefit to its citizens. So that the people of Bekasi City become more prosperous because every need and interest in their lives can be properly taken care of by the Government.